A meta‐analysis: microRNAs' prognostic function in patients with nonsmall cell lung cancer. (15th August 2017) - Yu, Na; Zhang, Qingjun; Liu, Qing; Yang, Jiayu; Zhang, Sheng
Abstract: Accumulating papers have demonstrated that microRNAs play an important role in the progression of lung cancer, mainly as oncogenic and tumor suppressive. Therefore, microRNAs may influence the survival of lung cancer patients. In this meta‐analysis, we evaluated the role of microRNAs in affecting the overall survival in nonsmall cell lung cancer ( NSCLC ) patients, which may provide valuable information for the treatment of nonsmall cell lung cancer. We used keywords to retrieve literatures from online databases PUBMED, EMBASE and Web of Science and included 12 studies into our investigation according to pre‐set criteria. Then, we analyzed the data with stata13.1 to evaluate the microRNAs role on the prognosis of NSCLC patients. NSCLC patients with higher microRNAs expression levels tend to show lower overall survival. HR (hazard ratio): 2.49, 95% CI (confidence interval): 1.84–3.37. Besides, both oncogenic and tumor suppressive microRNAs have an evident influence on prognosis with HR values of 2.60 (95% CI: 2.12–3.19) and 0.41 (95% CI: 0.05–0.34), respectively. microRNAs, especially from tissue, have an influence on overall survival of NSCLC patients, which indicates that microRNAs could serve as potential prognostic markers for NSCLC and may provide a treatment strategy for advanced NSCLC patients. Abstract : The article is different from other researches about miRNAs' function in cancer patients, which considered much miRNAs to evaluate its comprehensive influence as there were kinds of miRNAs existed in human body instead of only one or several kinds of them. So there was a new idea in it.